Ramucirumab in elderly patients with hepatocellular carcinoma and elevated alpha-fetoprotein after sorafenib in REACH and REACH-2 - Kudo, Masatoshi; Galle, Peter R; Llovet, Josep M; Finn, Richard S; Vogel, Arndt; Motomura, Kenta; Assenat, Eric; Merle, Philippe; Brandi, Giovanni; Daniele, Bruno; Okusaka, Takuji; Tomášek, Jiří; et al. (Liver international, 2020)
BACKGROUND & AIMS: Limited data on treatment of elderly patients with hepatocellular carcinoma (HCC) increase the unmet need. REACH and REACH-2 were global phase III studies of ramucirumab in patients with HCC after prior sorafenib, where patients with alpha-fetoprotein (AFP) ≥400 ng/mL showed an overall ssurvival (OS) benefit for ramucirumab. These post-hoc analyses examined efficacy and safety of ramucirumab in patients with HCC and baseline AFP ≥ 400 ng/mL by three prespecified age subgroups (<65, ≥65 to <75 and ≥75 years). METHODS: Individual patient data were pooled from REACH (baseline AFP ≥400 ng/mL) and REACH-2. Kaplan-Meier and Cox proportional hazards regression methods (stratified by study) assessed OS, progression-free survival (PFS), time to progression (TTP) and patient-reported outcomes (Functional Hepatobiliary System Index-8 [FHSI-8] score). RESULTS: A total of 542 patients (<65 years: n = 302; ≥65 to <75 years: n = 160; ≥75 years: n = 80) showed similar baseline characteristics between ramucirumab and placebo. Older subgroups had higher hepatitis C and steatohepatitis incidences, and lower AFP levels, than the <65 years subgroup. Ramucirumab prolonged OS in patients <65 years (hazard ratio [HR], 0.753; 95% CI 0.581-0.975), ≥65 to <75 years (0.602; 0.419-0.866) and ≥75 years (0.709; 0.420-1.199), PFS and TTP irrespective of age. Ramucirumab showed similar overall safety profiles across subgroups, with a consistent median relative dose intensity ≥97.8%. A trend towards a delay in symptom deterioration in FHSI-8 with ramucirumab was observed in all subgroups. CONCLUSIONS: In this post-hoc analysis, ramucirumab showed a survival benefit across age subgroups with a tolerable safety profile, supporting its use in advanced HCC with elevated AFP, irrespective of age, including ≥75 years.
Keywords: Carcinoma, Hepatocellular; humanizované monoklonální protilátky; Aged; Humans; výsledek terapie; sorafenib; Sorafenib; alfa-fetoproteiny; nádory jater; hepatocelulární karcinom; Treatment Outcome; alpha-Fetoproteins; Antibodies, Monoclonal, Humanized; Liver Neoplasms; lidé; senioři